2018
DOI: 10.1111/hel.12552
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of Helicobacter pylori infection among junior high school students in Grudziadz, Poland

Abstract: Background The purpose of the study was to assess the prevalence of Helicobacter pylori infection among the junior high school students in city Grudziądz, Poland. Materials and methods A prospective cross‐sectional study among second junior high school students was conducted from September 2008 to June 2015 during seven consecutive school years. The studied group was 3241 students 13‐17 years old. The 13C‐urea breath test (UBT) was administered to all participants for current H. pylori infection. Clinical, soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 23 publications
1
27
0
1
Order By: Relevance
“…Accordingly, H. pylori transmission is more highly associated with childhood living conditions than adult living conditions [9,10]. Previous studies have thus sought to identify select risk factors for H. pylori infection by examining childhood environments [10][11][12][13][14][15]. Common risk factors examined in these studies include age, indicators of socioeconomic status, and poor hand and cooking sanitation [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, H. pylori transmission is more highly associated with childhood living conditions than adult living conditions [9,10]. Previous studies have thus sought to identify select risk factors for H. pylori infection by examining childhood environments [10][11][12][13][14][15]. Common risk factors examined in these studies include age, indicators of socioeconomic status, and poor hand and cooking sanitation [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al reported a statistically significant decrease in the H pylori infection rate in symptomatic children between 2005 (25.6%) and 2017 (12.8%) in China. However, infection rates remain higher in some groups of children, dependent on factors such as low socioeconomic status and bad sanitary conditions as was concluded in studies from Poland, Peru, China, and Ethiopia …”
Section: Epidemiologymentioning
confidence: 90%
“…The epidemiology of H pylori is rapidly changing, as shown by the high number of epidemiologic studies published in the last year. The world prevalence of H pylori varies significantly, from 2.5% in Japan to 34.6% in Ethiopia (Table ). Nonetheless, a decreasing trend in the prevalence of H pylori infection among children is being observed.…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations